QTc prolongation during ciprofloxacin and fluconazole combination therapy: prevalence and associated risk factors. (6th December 2017) - Berger, Florine A.; Monadian, Nico; de Groot, Natasja M. S.; Santbergen, Bart; van der Sijs, Heleen; Becker, Matthijs L.; Broers, Annoek E. C.; van Gelder, Teun; van den Bemt, Patricia M. L. A.
Abstract : Aim(s): Ciprofloxacin and fluconazole combination therapy is frequently used as prophylaxis for, and treatment of, infections in patients with haematological malignancies. However, both drugs are known to prolong the heart rate‐corrected QT (QTc) interval, which is a serious risk factor for torsade de pointes (TdP). Therefore, the aim of the current study was to assess the prevalence of QTc prolongation during ciprofloxacin and fluconazole use. The secondary objective was to determine associated risk factors of QTc prolongation in these patients. Methods: A prospective observational study was performed in patients admitted to the Erasmus University Medical Centre and treated with ciprofloxacin and fluconazole. A 12‐lead electrocardiogram (ECG) was recorded at the estimated time to peak concentration (Tmax ) for the last added drug. The main outcome was the proportion of patients with QTc prolongation during treatment. Data on the following potential risk factors were collected: patient characteristics, serum electrolyte levels, dosage of ciprofloxacin and fluconazole, renal and liver function and concomitant use of other QTc‐prolonging drugs and cytochrome P450 3A4 inhibitors. Results: A total of 170 patients were included, of whom 149 (87.6%) were treated for haematological malignancies. The prevalence of QTc prolongation was 4.7%. No risk factors were found to be associated with QTc prolongation. The QTc interval increased by 10.7 ms [95% confidence interval (CI) 7.2, 14.1 ms] during ciprofloxacin and fluconazole combination therapy. Conclusion: The prevalence of QTc prolongation in patients using ciprofloxacin and fluconazole is low compared with the prevalence in the general population, which varies from 5% to 11%. In addition, no risk factors were found. Given the low prevalence, routine ECG monitoring in patients on this therapy should be reconsidered.